Política colonizadora de España en Alta California en la correspondencia de los padres Franciscanos 1769-1795 - Tóth, Ágnes (Acta Hispanica, 2008)
What were the reasons for the inability of the Viceroyalty of Spain to consolidate its power in Alta California? The aim of the essay is to provide an answer to this question, examining the interpretation of Franciscan fathers serving in missions of the region about the causes of that failure. The letters and other documents of the Franciscans—either unintentionally or consciously—represent a very modern point of view on power relations and government measures; they impeach the government for the lack of certain economic and commercial conditions that would encourage free trade and development in the region. In their interpretation, the essential prerequisite of development and wealth creation is the dilingent, continuous labor of the population. However, in the case of Alta California, this is hindered by the overregulation of commerce and the regulation of prices on behalf of the government. The Franciscans also note that as a result of the strict land ownership laws, the region does not attract much settlers, resulting in a decrease of urban development. Due to the lack of motivating factors, the main philosophy of the residents of the region is “maybe tomorrow”.